Effects of Dapagliflozin on Serum Low-Density Lipoprotein Cholesterol and Triglyceride Levels - Gürkan, Eren (European Journal of Therapeutics, 2023)
Objective: The aim of this study is to assess the effects of dapagliflozin, a sodium/glucose cotransporter 2 (SGLT2) inhibitor, on serum triglyceride and low-density lipoprotein (LDL) cholesterol levels in patients with type 2 diabetes mellitus (DM). Methods: A total of 40 patients with type 2 DM, who were followed up regularly in the Endocrinology and Metabolism Out-patient Clinic of State Hospital, were evaluated retrospectively. In these patients, dapagliflozin was added to their regular treatment for glycemic control. The patients’ anthropometric measurements, glycemic regulation status, and serum LDL cholesterol and triglyceride levels were retrieved from the system records. A statistical analysis of drug effects was performed using the repeated measures analysis of covariance test, keeping the effects of HbA1c and body mass index (BMI) covariates constant. Results: In addition to the improvement in fasting blood glucose levels, HbA1c, and body weight of the patients, a reduction by 10 mg/dL and 43.04 mg/dL was observed in serum LDL cholesterol and triglyceride levels, respectively. The evaluation of BMI and HbA1c covariates together revealed a statistically significant reduction in triglyceride levels (p=0.032 and p=0.008, respectively). Conclusion: Besides glycemic control and weight loss, addition of dapagliflozin to the type 2 DM therapy is associated with an improvement in serum triglyceride levels, suggesting that together with other benefits, SGLT2 inhibitors appear to provide an additional benefit of reducing the risk of cardiovascular diseases.